2011
DOI: 10.1080/13811118.2011.540213
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Life Events Proximal to Adult Suicide: A Synthesis of Findings from Psychological Autopsy Studies

Abstract: The objective of this review was to summarize and interpret data about adverse life events proximal to adult suicide from major psychological autopsy studies. A PubMed search was conducted. Nearly all suicides have experienced at least 1 (usually more) adverse life event within 1 year of death (concentrated in last few months). Controlled studies have revealed specific life events, notably interpersonal conflict, as risk factors for suicide with some evidence of a dose-response effect. Some of the risk is inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 50 publications
7
89
1
4
Order By: Relevance
“…Among the psychological factors, the association of any adverse life event within 1 year prior to death with increased risk for suicide is consistent with previous studies in China [4,6] and studies in both developed and developing countries [7,[63][64][65][66][67] . Although the underlying mechanism between adverse life events and suicide remains unclear, according to the stress-diathesis model, adverse life event(s) can trigger a series of genetic, physiological, and psychological changes including the modification of gene expression through DNA methylation [1,53,[68][69][70] .…”
Section: Issn 2372-5923supporting
confidence: 75%
“…Among the psychological factors, the association of any adverse life event within 1 year prior to death with increased risk for suicide is consistent with previous studies in China [4,6] and studies in both developed and developing countries [7,[63][64][65][66][67] . Although the underlying mechanism between adverse life events and suicide remains unclear, according to the stress-diathesis model, adverse life event(s) can trigger a series of genetic, physiological, and psychological changes including the modification of gene expression through DNA methylation [1,53,[68][69][70] .…”
Section: Issn 2372-5923supporting
confidence: 75%
“…This finding is consistent with the extant literature that suggests that interpersonal conflict is a strong generic predictor of suicide. A review of the psychological autopsy studies found that interpersonal conflict affected the risk for suicide in a dose-response manner [54].…”
Section: Discussionmentioning
confidence: 99%
“…Financial difficulties (Stack and Wasserman, 2007), concern over work prospects or job loss (Almasi et al, 2009;Høyer et al, 2009), relational problems (Foster et al, 1999;Foster, 2011) traumatic events such as sexual abuse, bullying, victimization and conflict (Klomek et al, 2009;Maniglio, 2011;O'Neill et al, 2014) have all been implicated in the aetiology of suicidal behaviour. Yet, singular forms of adversity are unlikely to transpire in isolation since individuals typically encounter numerous stressors or multiple types of stressors at different periods over their lifetime.…”
Section: Introductionmentioning
confidence: 99%